Tingkat Kepuasan Pasien Rawat Jalan Terhadap Mutu Pelayanan Kesehatan Di Unit Poli Umum Puskesmas Bolou Kecamatan Sabu Timur Tahun 2023 - Heni Bangngu Dimu (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Patient satisfaction embodies patient loyalty to health services that can provide maximum service quality. Calculating the level of patient satisfaction is an indicator of the quality of health services. The total number of outpatients visiting the Bolou Community Health Center in 2020 was 6,477, in 2021 there were 3,571, in 2022 there were 1,834 and in 2023 there were 3,970. This shows that over the last four years patients visiting the Bolou Community Health Center have decreased. The decline that occurred in the level of outpatient satisfaction in the General Poly Unit was 42% in 2021, 35% in 2022, and 27% in 2023. To find out the description of outpatient satisfaction in the General Poly Unit which includes the dimensions of tangible, reliability, responsiveness, assurance and empathy, this research was conducted. The type of research used is quantitative research with a descriptive design where this research is carried out with the aim of describing an objective condition. The population in this study was all outpatients at the General Polyclinic in 2023, totaling 3,970 patients. The sample in this research was an accidental sampling technique, namely 94 samples. The questionnaire measuring tool is the instrument in this research. Univariate analysis is the analysis used in research. research results, the description of the tangible aspect with the most indicator achievements expressed satisfaction (70.2%), the description of the reliability aspect with the most indicator achievements expressed satisfaction (58.5%), the description of the responsiveness aspect with the most indicator achievements expressed dissatisfaction (52.1%) , the description of the assurance aspect with the most indicator achievements expressed satisfaction (61.7%), the description of the empathy aspect with the most indicator achievements expressed satisfaction (53.2%).